BULL VS BEAR MARKET- AN INVESTMENT GAME ANALYSIS USING MOVING AVERAGE METHOD - Rout, Biswajit; Mohanty, Ayesha; Kacharia, Akash Kumar (International Journal of Research -GRANTHAALAYAH, 2017)
This paper aims to analyse and interpret the investor perception about investing in stock market. The market is often referred as to bull or bear market. This is key importance for financial decisions and economic analysis. The market behaves differently in these two phase. The bull market is identified when there is constant rise of stock prices whereas bear market is referred when there is fall in stock prices. These phases occur due to different trends of market or economy. Investor sentiments get affected by this. The paper tries to identify and provides understanding about the factors that causes and how it affects the psychology of investors. There are different analysis techniques used by analysts. The popular and common analysis theories are Fundamental Analysis and Technical Analysis. This paper is based on technical analysis of different category of stock with respect to wide spread industry like FMCG sector, Banking sector, Oil and Natural Gas sector, Automobiles sector and Pharmaceutical Sector etc. The paper also tries to establish whether the market is having a Bull Run or bear. The movement of stock prices is analysed in technical analysis. The data of stock prices are collected from NSE official site. The analysis in done for 5 years span starting from April 2012 to Mar 2017. Even to understand better, analysis of the stock is done on 100days moving average. Prevailing news during those times are also considered to interpret the behaviour of the investors.